2017
DOI: 10.1007/s10035-017-0769-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of sedimentation of non-cohesive particles via CFD–DEM simulations

Abstract: The sedimentation process of granular materials exists ubiquitously in nature and many fields which involve the solid-liquid separation. This paper employs the coupled computational fluid dynamics and discrete element method (CFD-DEM) to investigate the sedimentation process of non-cohesive particles, including the hindered settling stage and the deposition stage. Firstly, the coupled CFD-DEM model for sedimentation is validated by the hindered settling velocity at different solid volume concentrations of susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…This solver was developed by Xiao and Sun (2011) based on two open-source codes: (a) the CFD toolbox OpenFOAM (OpenCFD, 2013) and (b) the molecular dynamics simulator LAMMPS (Plimpton, 1995). SediFoam has been demonstrated to be a capable tool in simulating many particle flow problems, e.g., a fluidized bed (Xiao and Sun, 2011;Gupta, 2015), sediment transport (Sun and Xiao, 2016), and sedimentation (Xu et al, 2018;Sun et al, 2018), etc. In these areas, the mathematical models mentioned above for the particle motion, fluid flow, and the interaction force have been verified and extensively validated.…”
Section: Fluid-particle Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This solver was developed by Xiao and Sun (2011) based on two open-source codes: (a) the CFD toolbox OpenFOAM (OpenCFD, 2013) and (b) the molecular dynamics simulator LAMMPS (Plimpton, 1995). SediFoam has been demonstrated to be a capable tool in simulating many particle flow problems, e.g., a fluidized bed (Xiao and Sun, 2011;Gupta, 2015), sediment transport (Sun and Xiao, 2016), and sedimentation (Xu et al, 2018;Sun et al, 2018), etc. In these areas, the mathematical models mentioned above for the particle motion, fluid flow, and the interaction force have been verified and extensively validated.…”
Section: Fluid-particle Interactionsmentioning
confidence: 99%
“…The value of the inter-particle contact force is larger in the higher-speed flow, represented by the larger-diameter cylinder with the darker colour. Moreover, we calculate the value of averaged contact stress σ con on the y-z planes proposed by Xu et al (2018), which increases obviously with the fluid velocity, as shown in Fig. 19.…”
Section: Jamming Domementioning
confidence: 99%
“…The lift force, including Saffman lift forces and Magnus lift forces, accounts for the lift or upward force due to particle rotation. In the process of particle sedimentation, particles may fall in the vertical direction with rather little acceleration, in which the effect of lift force and virtual mass force could be neglected [17]. Hence, in the present simulation, only the drag force and pressure gradient force are considered.…”
Section: Governing Equations Of Cfd and Fluid-particle Intercationmentioning
confidence: 99%
“…ε −χ+1 in Equation (5) denotes the porosity correction function to consider the presence of other particles in the flow system, as proposed by Di Felice [17]:…”
Section: Governing Equations Of Cfd and Fluid-particle Intercationmentioning
confidence: 99%
“…In this way, the interparticle collisions play a fundamental role. The dynamics of collective granular packing is addressed in the context of cake formation for spherical particles [21,22]. However, as far as we know, no information is available in case of nonspherical nonconvex grains.…”
Section: Introductionmentioning
confidence: 99%